Mnenja slovenskih in nizozemskih delovnih terapevtov o kognitivnem pristopu v procesu učenja učinkovitega izvajanja vsakodnevnih aktivnosti - Korelc, Simona (Rehabilitacija (Ljubljana), 2020)
Background: The Cognitive Orientation to Daily Occupational Performance approach (CO-OP) is a client-centreed individual therapeutic approach. The authors developed it for children with developmental coordination disorder (DCD). As this approach has become established in clinical practice in recent years, we wanted to identify the possible differences in the treatment of children with DCD between occupational therapists in Slovenia and the Netherlands. Methods: We invited three occupational therapists from both countries for qualitative research and conducted a semi-structured interview with them. Interview records were analysed according to the principles of qualitative content analysis. Results: Among the strengths of the CO-OP approach, all therapists emphasised the transfer of learned strategies to other activities performed by the child, independent choice of goals, parental involvement and active participation of the child. According to the therapists, the most challenging part of carrying out the process is to verbally guide the child without placing the child in a specific position, involving the parents and choosing appropriate instruments assessment. The largest differences in the use of the CO-OP approach were found in the referral diagnosis and procedure of children, use of assessment instruments, equipment and competencies of occupational therapists used. Conclusion: Content analysis of the opinions of the occupational therapists showed that they felt that the CO-OP approach was effective and useful. Further, it has many advantages in dealing with children with DCD. However, there may also be some obstacles in clinical practice that make it difficult to implement.
Keywords: Activities of Daily Living; Child; Cognitive Orientation to Daily Occupational Performance approach; CO-OP; de Morton Mobility Index; delovni terapevt; developmental coordination disorder; experiences; izkušnje; occupational therapist; Occupational Therapy; otrok; razvojna motnja koordinacije; rehabilitation